Fc-saxatilin suppresses hypoxia-induced vascular leakage by regulating endothelial occludin expression - Choi, Hyun-Jung; Kwon, Il; Kim, Na-Eun; Kim, Jayoung; An, Sunho; Kang, Sungsoo; Hong, Sung-Yu; Nam, Hyo Suk; Hoe Heo, Ji (Thrombosis and Haemostasis, 2017)
Vascular leakage due to compromised integrity of the endothelial barrier is closely associated with brain damage in several neurological disorders, including ischaemic stroke. Saxatilin, a snake venom disintegrin containing the Arg-Gly-Asp (RGD) motif, exerts thrombolytic and antiplatelet effects by interacting with multiple integrins on platelets. Integrin signalling is indispensable for regulation of endothelial permeability. Saxatilin may play a role in vascular leakage after ischaemia because it has high affinity for endothelial integrins. Here, we determined whether Fc-saxatilin, an Fc-fusion protein of saxatilin, could prevent vascular leakage under hypoxic or ischaemic conditions. In mouse brain microvascular endothelial cells, hypoxia increased the permeability to FITC-dextran, and this effect was attenuated by Fc-saxatilin treatment. Fc-saxatilin also blocked vascular leakage of Evans Blue in the ischaemic brain induced by middle cerebral artery occlusion in mice. Furthermore, the expression of occludin, a tight junction protein, was reduced by hypoxia in endothelial cells. This downregulation of occludin was attenuated by Fc-saxatilin treatment. We also determined the activity of matrix metalloproteinases (MMPs) 2 and 9 because they are implicated in the degradation of occludin and of the microvascular basal lamina. Hypoxia increased MMP-9 activity, and this increase was attenuated by Fc-saxatilin treatment. Fc-saxatilin specifically bound to integrin αvβ3 of the endothelial cells and inhibited hypoxia-induced activation of FAK, a downstream signalling molecule in integrin-dependent signal transduction. Taken together, these results provide new insights into the mechanism via which Fc-saxatilin, as an integrin antagonist, prevents vascular leakage under ischemic conditions by regulating occludin expression in endothelial tight junctions.Supplementary Material to this article is available online at www.thrombosis-online.com.
Keywords: Fc-saxatilin; disintegrin; occluding; endothelial permeability